Optimal Modification of Helical Gear Tooth Surface based on KISSsoft - Wang Chunyan; Shi Pengzhen (Jixie chuandong)
Considering the influence of deformation and displacement of supporting device on modification results,the gear modification is carried out by using KISSsoft analysis software,the gears are modified in generally drum shape and spiral with drum shape respectively,according to Weber slice theory,the stiffness matrix of displacement of tooth contact is established,by using the way of permutation and combination of incremental,the Hertz pressure stress,transmission error,peak load distribution coefficient of tooth meshing performance data of gear under different amount of modification are obtained,considering the deformation and displacement of the supporting device of the gear system accords with the actual working environment,comparing the two kinds of modification of gear meshing performance,contact stress,transfer the error of peak,longitudinal load distribution coefficient than the average crown modification to the tooth surface with drum shaped spiral gears,gear modification in improving the full use of the carrying capacity essential.